Dry anaerobic digestion of ammoniated straw: Performance and microbial characteristics. (May 2022) - Tang, Fangyi; Tian, Jun; Zhu, Nengwu; Lin, Yunqin; Zheng, Haomin; Xu, Zhiyong; Liu, Weizhen
Graphical abstract: Highlights: An ammoniated straw-to-biogas residue ratio of 3:3 (TS) generates the most methane. The lag time shortens when a higher proportion of biogas residue is added. The hydrolytic acidifying bacteria mainly comprised Firmicutes and Bacteroides. Methanosarcina mainly produced methane, and Methanobacterium prevented acidification. Abstract: This paper explores the influence of the mixing ratio of ammoniated straw to biogas residue on the stability and methane yield of dry anaerobic digestion and analyzes the structure of the microbial community with digestion time. Five reactors containing ammoniated straw and swine manure biogas residue at ratios of 5:1, 4:2, 3:3, 2:4 and 1:5 (total solids) were constructed, and neither total ammonia nitrogen nor free ammonia nitrogen was inhibited. Three reactors produced gas successfully. The reactor with a ratio of 3:3 (R3-3) yielded the best methane production, with a cumulative methane production of 115.13 mL/(g·VSadded ). Analysis of the R3-3 microbial community showed that bacteria were dominant species. Archaea, mainly Methanosarcina, played an important role in anaerobic digestion and methane production. Methanobacterium, with high acid tolerance, was positively related to total volatile fatty acids (TVFA), playing a key role in preventing the acidification of the anaerobic digestion system.